Gambaran Penggunaan Obat Narkotika di Depo Farmasi Rawat Jalan Rumah Sakit X Kota Pekanbaru - Mevy Trisna; Renatalia Fika; Amalia Rahmi (Program Studi DIII Farmasi Akademi Farmasi Dwi Farma, 2024)
Narcotics are substances or drugs derived from plants, either synthetic or semi-synthetic, which are used to relieve pain and can cause addiction. Narcotics use requires stricter supervision to avoid drug abuse. The aim of this research is to determine the description of the use of narcotics drugs hospital X Pekanbaru city Outpatient Pharmacy Depot for the period August - October 2022. This research is descriptive and data collection was carried out retrospectively. The sampling technique used was purposive sampling. The results of research on the use of narcotic drugs conducted in the period August – October 2022 showed that based on gender, there were 107 prescriptions for men (48.2%) and 115 prescriptions for women (51.8%). Narcotics use based on age was highest in patients over 45 years old with 84 prescriptions (37.84%). The most commonly prescribed use based on the name of the preparation was codeine 15mg with 2,003 tablets (47.05%). The highest use based on prescriptions from specialist doctors was lung specialist doctors with 102 prescriptions (45.94%).